INVESTMENT FRAMEWORK FOR CIRCULAR PACKAGING MANAGEMENT IN SUSTAINABLE BUSINESS DEVELOPMENT - Kysil, Katherina; Derhachova, Victoriia (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The article examines the investment framework for circular packaging management as a component of sustainable business development under conditions of economic instability and Ukraine’s post-war recovery. The study substantiates the need to transition from the traditional linear economic model to a circular economy approach based on the reuse, recycling, and retention of materials within production cycles. Particular attention is paid to enterprises in the food and beverage industry, using PJSC “Obolon” as a case study, due to their intensive use of packaging materials and significant environmental impact. Circular packaging management is considered as an integrated investment system that includes collection, logistics, processing, management, and system support components. The paper identifies the main sources of financing for circular initiatives, including internal funds, bank loans, partner investments, public support programs, and international grant funding. The risks associated with the implementation of circular projects and the role of international recovery initiatives in creating a favorable investment environment are also analyzed. The findings demonstrate that effective investment support for circular packaging management contributes to improved economic performance, reduced environmental impact, and the achievement of the Sustainable Development Goals.